Asymptomatic Congenital Syphilis with Bilateral Metaphysitis in a Term Neonate: A Case Report - Daffa Fahreiza; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Congenital syphilis is a transplacental infection caused by Treponema pallidum that is associated with significant fetal and neonatal morbidity and mortality. Although many infected neonates appear clinically asymptomatic at birth, active infection may only be identified through serological and radiological evaluation. This report describes a 3-day-old full-term female neonate born at 37 weeks of gestation by cesarean section due to cephalopelvic disproportion, premature rupture of membranes, and maternal syphilis. The mother had not undergone antenatal syphilis screening or received treatment during pregnancy despite having a reactive Venereal Disease Research Laboratory (VDRL) test at delivery. The neonate appeared clinically well without dysmorphic features, respiratory distress, or other classic manifestations of congenital syphilis. However, laboratory evaluation revealed leukocytosis and persistently reactive VDRL titers of 1:64 on the first and third days of life. A skeletal survey demonstrated bilateral metaphysitis involving the distal radius, ulna, and first metatarsal base without periostitis or pathological fractures, consistent with early syphilitic osteochondritis. Initial empirical treatment with ampicillin and gentamicin was subsequently changed to benzathine penicillin G after the diagnosis was confirmed. This case highlights that congenital syphilis may present as subclinical skeletal involvement despite an apparently healthy neonate. Routine antenatal screening, prompt neonatal serological assessment, targeted skeletal imaging, and appropriate post-treatment follow-up are essential for early diagnosis, timely management, and prevention of long-term complications, particularly in resource-limited healthcare settings.